Chicken Ranch - Broomfield, Nicholas; Sissel, Sandi (Metrodome, 2005)
For his first full-length feature, Nick Broomfield travelled to the Nevada desert with his camerawoman Sandi Sissel, to the world’s only brothel-with-an-airstrip. The "Chicken Ranch" sat in the middle of nowhere, serving passing truckers and groups of Japanese tourists who would be shipped in from Las Vegas using the Ranch’s own private plane ... So Broomfield and Sissel lived in the brothel – little more than a series of trailers jammed together – for two months, filming the girls, their clients and the owners in arrestingly intimate style. [www.thespinningimage.co.uk]
Keywords: DVD-Video